ANALISIS PENGARUH ATTRACTION, ACTIVITY, DAN AMENITY TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN MUSEUM TEKSTIL JAKARTA - Jane Cristie; Roels Ni Made Sri Puspadewi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Every year the number of tourists visiting the Textile Museum has decreased. The decision to visit tourists can be influenced by tourist attractiveness. Attraction has several components in it attraction, accessibility, activity, amenities and ancillary. The purpose of this study was to determine the effect of tourist attractions, activities, and amenities on the decision to visit the Textile Museum tourism object. This research method uses quantitative methods and uses multiple linear regression analysis with the help of SPSS 25 software. The population in this study are tourists visiting the Textile Museum with a sample of 100 respondents. Based on research that attraction has a positive and significant effect on visiting decisions with a t count of 2.917 > t table of 1.984. Partially activity influences the decision to visit with a t count of 3.963 > t table of 1.984. The amenity variable influences the decision to visit with a t count of 4.698 > t table of 1.984. Simultaneously attraction, activity and amenity have a positive effect on the decision to visit tourists to the Jakarta Textile Museum with a calculated f value of 95.332 > from f table 2.70 with this value it is known that H0 is rejected and Ha is accepted. Attraction, activity and amenity variables, the correlation value of determination is obtained 0.749 or 74.9% meaning that the variables of attraction, activity and amenity influence the decision to visit tourists to the Textile Museum by 74.9%, while the remaining 25.1% is influenced by other variables which is not researched. Based on the results of this study it can be concluded that there is a relationship between attraction, activity and amenities on the decision to visit tourists. If attraction, activity and amenities are well improved then it can increase the decision to visit the Textile Museum.